Navigating English Tense Challenges: A Gap Analysis for Non-English Major Students' Language Acquisition - Ariani Rosadi; Prodi Ilmu Komunikasi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study comprehensively investigated the gap in English tense mastery among non-English students. Data were collected using a qualitative case study methodology from seven purposively selected informants through in-depth interviews and direct observation. Key findings reveal persistent challenges, including significant anxiety around using complex tenses, the widespread influence of mother tongue interference (given the absence of explicit tense conjugations in Indonesian), and the limited effectiveness of traditional non-contextual grammar teaching. The observations also highlight a critical gap: although students use digital devices extensively, their engagement with English content is minimal, directly contributing to lower writing and speaking practice assessment scores. Instead, the unexpected finding was the student's remarkable ability to internalize the 16th pattern of the English tenses through memorization in just thirty minutes. These insights underscore the urgent need for innovative, contextual, and confidence-building pedagogical strategies to bridge the gap between theoretical understanding and practical application, enhancing language acquisition and professional communication skills.